Validity and reliability of the Chinese version of the Jenkins Sleep Scale among university students in China - Mengyuan Zhao; Garry Kuan; Ke Zhou; Yee Cheng Kueh (PeerJ)
Background The Chinese version of the Jenkins Sleep Scale (JSS-C) is widely used; however, it lacks formal validation, and its applicability to Chinese university students has not been examined. This study evaluated the validity and reliability of the JSS-C in this population, with a focus on gender differences. Methods A cross-sectional study was conducted with 1,534 Chinese university students (29.6% male, 70.4% female; mean age = 19.83 ± 1.54 years) recruited through convenience sampling. Participants completed the JSS-C, which assesses sleep disturbances across four key domains. Confirmatory factor analysis was used to examine construct validity. Internal consistency (Cronbach’s alpha) and composite reliability (CR) were calculated to assess reliability. Measurement invariance testing across gender groups was conducted to evaluate the scale’s robustness. Results Confirmatory factor analysis supported a strong one-factor structure for the JSS-C, with excellent model fit indices (χ2/df = 1.82, Tucker-Lewis index (TLI) = 0.997, comparative fit index (CFI) = 0.999, standardized root mean square residual (SRMR) = 0.007, root mean square error of approximation (RMSEA) = 0.023), exceeding conventional thresholds. Reliability analysis showed high internal consistency (Cronbach’s alpha = 0.840) and composite reliability (CR = 0.844), indicating strong scale stability. The JSS-C also demonstrated full measurement and structural invariance across genders, confirming its unbiased applicability for both male and female students. Conclusion The JSS-C is a brief, valid, and reliable instrument for assessing sleep disturbances among Chinese university students. Its standardized scores support meaningful gender-based comparisons.